Can SMS technology improve low take-up of social benefits? (2014)
Low take-up of stigma-free social benefits is often blamed on information asymmetries or administrative barriers. There is limited evidence on which of these potential channels is more salient in which contexts. We designed and implemented a randomized controlled trial to assess the extent to which informational barriers are responsible for the prevalent low take-up of government benefits among Colombian conflict-driven internal refugees. We provide timely information on benefits eligibility via SMS to a random half of the displaced household that migrated to Bogotá over a 6-month period. We show that improving information increases benefits' take-up. However, the effect is small and only true for certain type of benefits. Hence, consistent with previous experimental literature, the availability of timely information explains only part of the low take-up rates and the role of administrative barriers and bureaucratic processes should be tackled to increase the well-being of internal refugees in Colombia. © 2014 by Walter de Gruyter Berlin Boston 2014.